Elements of natural logic for the study of unnoticed misunderstanding in a communicative approach to learning - Kohler, Alaric (My University, 2015)
The following study my not actually relates to the Conference Theme, in particular to the Contemporary Public Discourse, yet the audience may find relevant links between their own analysis and the methodological proposal for analyzing misunderstandings presented here. Misunderstandings are part of the everyday life, and have been since long ago among the research topics of linguistics, pragmatics, psycholinguistics and other studies of language and communication, notably in relation to ambiguity (p.ex. Caron, 1983). Misunderstanding, however, is more a common sense notion, and any attempt to define it clearly is confronted with the difficulty to set criteria delimiting misunderstanding from other forms of ambiguity or the general attempt to build a mutual understanding. Verdonik (2010), for instance, reports some relative borderline examples of misunderstanding. Sayer (2013) tries to specify the relations between misunderstanding and mutual comprehension. Bazzanella & Damiano (1999) have studied the way interlocutors handle misunderstanding in their conversation, and distinguish “non- understanding” from “misunderstanding”, and “understanding” from “coming to understanding”, i.e. building a common understanding. They insist on the importance to approach understanding or coming to understanding as a continuum rather than something that is or isn't. in this approach, misunderstanding are considered as participating to the construction of mutual understanding in the communication. Linell (1995) distinguishes mishearing, misunderstanding, misinterpreting, and so on. Generally, language-based analysis of misunderstanding identify the occurrence of a misunderstanding in a given discourse or interaction from the presence of a reparation (Weigand, 1999; Dascal, 1999). There are only few exceptions to this way of proceeding, as for example the work of Trognon & Saint-Dizier (1999) who also refer to the cognitive aspect of communication in order to investigate misunderstanding. Yet, event in this last example, it is a reparation much later in the conversation that allows the researcher to identify a misunderstanding. Yet, recent research shows that the inconsistencies in the communication are often overlooked by the participants (Galantucci & Roberts, 2014), which is an indicator that any analysis only based on explicit repair are missing quite many misunderstanding, unspoted by the interlocutors. What about situations where the gap between the interpretation of one and the other interlocutor is unnoticed? This last question takes a particular importance in the educative context. Research in sociology (Bourdieu et al., 1965; Bourdieu & Passeron, 1970; Passeron, 1991; Bourdieu et al., 1994; Bautier & Rochex, 1997; Bautier & Rayou, 2009) have pointed out misunderstanding as a candidate explanation for the reproduction of inequalities, as a general mechanism of our western school systems. For these authors, the differences between social classes in terms of communicative abilities, interpretation frame, pragmatic expectation and other features of the social interactions taking place in a school context, could be a major reason for the children originating from lower social classes and migration to have overall poorer school performances. To put this hypothesis into further investigation, and in particular into more micro-level analysis, requires to study misunderstanding in a school context. Yet, before to address the question of thereproduction of social inegality through misunderstanding, a more basic challenge needs to be taken: how can we observe misunderstanding, and, in particular, when these misunderstanding are unnoticed by the interlocutors involved in the interaction? My standpoint in this presentation is methodological, and consists in showing that Natural Logic can contribute to make some advance into this challenging question. Campos (sous presse) shows how Natural Logic is a theory and methodology relating discourse, meaning, and cognitive psychology (in particular, the piagetian theory). Natural Logic can be used for what Piaget (1972) calls a transdisciplinary approach, articulating the cognitive dimension of language use, the discourse and the meaning, and the interlocutory dynamics of social interactions. In this presentation, I will try to show how such an approach can study misunderstanding as simultaneously discrepancies in the meaning – the discursive – a learning issue – the psychological – and a collective construction here and now in the social interaction taking place at school – the interlocutory dynamics. Examples of misunderstanding will be taken from the presenter's PhD research on misunderstanding in a physics class at college (Kohler, 2015). References Bautier, E., and Rayou, P., (2009). Les inégalités d'apprentissage : programmes, pratiques et malentendus scolaires. Paris : Presses Universitaire de France. Bautier, E., and Rochex, J.-Y. (1997) Ces malentendus qui font les différences. In: Terrail, J.-P. (Ed.), La scolarisation de la France, Critique de l'état des lieux, Paris, La Dispute. Bazzanella, C., and Damiano, R. (1999). The interactional handling of misunderstanding in everyday conversations. Journal of Pragmatics, 31, 817-836. Bourdieu, P., and Passeron, J.-C., (1970). La reproduction. Eléments pour une théorie du système d'enseignement. Paris, Minuit. Bourdieu, P., Passeron, J.-C., and De Saint Martin, M., (1994). Academic Discourse: Linguistic Misunderstanding and Professorial Power. Standford: Stanford University Press. Bourdieu, P., Passeron, J.-C., and de Saint-Martin, M., (1965). Rapport pédagogique et communication. Paris: Mouton & Co, The Hague and Ecole Pratique des Hautes Etudes. Campos, M.N., (sous presse). Navegar é Preciso. Comunicar é Impreciso. São Paulo : EDUSP - Presses de l'Université de São Paulo. Caron, J., (1983). Les régulations du discours. Paris: PUF. Dascal, M. (1999). Introduction: Some questions about misunderstanding. Journal of Pragmatics, 31, 753-762. Galantucci, B., and Roberts, G. (2014). Do We Notice when Communication Goes Awry? An Investigation of People’s Sensitivity to Coherence in Spontaneous Conversation. PLOS ONE, 9. Grossen, M. (2010). Interaction analysis and psychology: A dialogical perspective. Integrative Psychological and Behavioral Science, 44, 1-22. Kohler, A. (submitted). Approches psychologiques de situations de malentendu dans des activités de didactique des sciences. Thèse de Doctorat en Sciences Humaines, Université de Neuchâtel, Suisse. Linell, P. (1995) Troubles with mutualities: toward a dialogical theory of misunderstanding and miscommunication. In: Marková, I., Graumann, C., and Foppa, K. (Ed.), Mutualities in dialogue, Cambridge: Cambridge University Press. Passeron, J.-C., (1991). Le raisonnement sociologique. L'espace non-poppérien du raisonnement naturel. Paris, Nathan. Piaget, J. (1972) L’épistémologie des relations interdisciplinaires. In: OCDE (Ed.), L’interdisciplinarité : Problèmes d’enseignement et de recherche dans les universités, Paris: OCDE. Sayer, I.M. (2013). Misunderstanding and language comprehension. Procedia - Social and Behavioral Sciences, 70, 738 – 748. Trognon, A., and Saint-Dizier, V. (1999). L'analyse conversationnelle d'un malentendu : le cas d'un dialogue tutoriel. Journal of Pragmatics, 31, 787-815. Verdonik, D. (2010). Between understanding and misunderstanding. Journal of Pragmatics, 42, 1364-1379. Weigand, E. (1999). Misunderstanding: The standard case. Journal of Pragmatics, 31, 763-785.
, Fifth International Symposium on Discourse, representations, argumentation (COMMUNALIS ), "Contemporary Public Discourse: Semiological, Argumentative and Rhetorical New Models", Alexander I.Cuza University, Iaşi, Roumania
Keywords: situation of misunderstanding unnoticed misunderstanding natural logic